(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article examines the issue of combining national values ​​and modern technologies in the primary education system in the era of digital transformation. The study analyzes the best practices of countries such as Japan, Singapore, South Korea, Estonia, and Canada, and shows ways to integrate traditional pedagogical heritage with modern digital tools. As a result, practical recommendations for the education system of Uzbekistan are formulated.